2022
DOI: 10.3389/fonc.2022.882230
|View full text |Cite
|
Sign up to set email alerts
|

Range-shifter effects on the stray field in proton therapy measured with the variance–covariance method

Abstract: Measurements in the stray radiation field from a proton therapy pencil beam at energies 70 and 146 MeV were performed using microdosimetric tissue-equivalent proportional counters (TEPCs). The detector volumes were filled with a propane-based tissue-equivalent gas at low pressure simulating a mean chord length of 2 μm in tissue. Investigations were performed with and without a beam range shifter, and with different air gaps between the range shifter and a solid water phantom. The absorbed dose, the dose-mean l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is probably due to the fact that the range shifter is positioned within line of sight from position D. The absorbed dose measured at position A with the Sievert was also shown to increase up to a factor of nine when introducing a range shifter. This increase is probably not due to neutrons but due to protons from the range shifter as discussed in detail in ( 23 ).…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This is probably due to the fact that the range shifter is positioned within line of sight from position D. The absorbed dose measured at position A with the Sievert was also shown to increase up to a factor of nine when introducing a range shifter. This increase is probably not due to neutrons but due to protons from the range shifter as discussed in detail in ( 23 ).…”
Section: Resultsmentioning
confidence: 88%
“…The absorbed dose measured at position A with the Sievert was shown to increase with increasing air gap. This increase is probably not due to neutrons but due to protons from the range shifter as discussed in detail in ( 23 ).…”
Section: Resultsmentioning
confidence: 88%
“…Previous studies on the increased neutron exposure from the use of a RS have demonstrated a two-or threefold increase in doses compared to similar irradiations without the RS. 7,8 However, it is important to note that these studies were based on measurements of H* (10) in the treatment room, and this scenario may not be representative for what happens inside the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the RS becomes an additional external source of neutrons during the proton treatment, increasing the out‐of‐field doses in proton patients, especially when taking into account the high radiobiological effectiveness of neutrons. Even though in PBS the out‐of‐field neutron dose is relatively small, 6 measurements in air and inside an anthropomorphic phantom during irradiations with a RS showed that this element could increase the production of neutrons by a factor of around 2 or 3, 7,8,9 while the overall neutron production in PBS is lower than in passive scattering delivery. Therefore, the evaluation of the contribution of RS neutrons in the patient is warranted.…”
Section: Introductionmentioning
confidence: 99%